Determinants of Selected Agricultural Export Crops in Nigeria: An Ecm Approach (2007)
This study examines the factors that determine the export performance of three major agricultural exportable commodities of cocoa, rubber and palm-kernel in the context of liberalization. Using time series data covering thirty-three years and to avoid spurious result, error correction model was applied in the analysis. The unit root test is in line with the a priori expectation that macroeconomic variables are not stationary at their level. Virtually all the variables tested were differenced once before attaining stationarity. Each of the three equations indicated that the dependent variables cointegrated with their arguments at 1 percent level. There is the existence of short term and long term equilibrium relationships between the dependent variables and their determinants. The results of the parsimonious error correction specifications showed that the previous year’s output and the net value of world trade negatively affect cocoa exports at 1 percent level while the previous year’s GDP positively contributes to cocoa exports at 5 percent. The lagged price ratio reduces rubber exports significantly at 5 percent but the real exchange rate significantly increases the export performance of rubber at 10 percent level. The previous year’s exports of palm kernel and the real GDP contributed positively to palm-kernel exports at 5 percent level while the lagged premium and palm kernel output negatively contributed to its export at 5 percent and 10 percent respectively. Promotion of agricultural exports is essential to reduce the burden of dependence on oil exports